Assessing Window Design's Impact on Daylight Uniformity in Classrooms in Patna, India - Maurya, Alok Kumar; Kumar, Ravish; Kumar, Ajay (Engineering, Technology & Applied Science Research, 2023)
Windows play a vital role in daylight infusion, significantly impacting indoor visual comfort. Various metrics exist for evaluating visual comfort in which the uniformity ratio falls under the distribution category and is as crucial as illuminance levels. This ratio effectively reduces the likelihood of glare and the need for artificial lighting. The primary objective of this research is to assess the impact of window design on daylight uniformity ratio in a classroom setting. In pursuit of this objective, a study investigated the uniformity ratio (Uo) of north-oriented and south-oriented classrooms of Kendriya Vidyalaya (KV) Khagual, Patna. The study considered five common shapes of windows (excluding the existing base cases) at different window-sill levels. Ninety simulations were run in the DesignBuilder software under overcast, intermediate, and clear sky conditions. To assess the uniformity ratio on three dates: March 21st, June 21st, and December 21st, which correspond to the highest, equinox, and lowest solar availability during the year under intermediate and clear sky conditions at three distinct times. The omission of the specific time and date for overcast conditions and the particular year for clear and intermediate sky conditions is justified as the outcome remains consistent throughout all years. The results show that the window design and sill level significantly affect the uniformity ratio. The research findings show that window design in Case 9 at a sill of 1230 mm and lintel of 3050 mm (just below the slab) consistently produces the best uniformity ratio across all sky conditions, independent of classroom orientation. This paper offers valuable design recommendations by comparing the uniformity ratio for five commonly used window designs. This is one of the first studies of window design and position to evaluate the uniformity ratio in the classrooms at Patna.